Whitewood Gully flows toward the River - Branch Cultural Historical Association (2010)
Early in the salt cod fishery, rinds (strips of bark) were used to cover fish in wet weather. The banks of the Whitewood Gully had a good supply of spruce and fir trees large enough to provide four and five foot rinds. When the bark was peeled, the trees died and were known as whitewoods, giving the gully its name.